2019
DOI: 10.1007/s11368-019-02299-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining contemporary and historical sediment sources in a large drainage basin impacted by cumulative effects: the regulated Nechako River, British Columbia, Canada

Abstract: Purpose Sediment dynamics in most large river basins are influenced by a variety of different natural and anthropogenic pressures, and disentangling these cumulative effects remains a challenge. This study determined the contemporary and historical sources of fine-grained (< 63-μm) sediment in a large, regulated river basin and linked changes in sources to activities in the basin. The river has seen declines in chinook salmon, sockeye salmon, and the endangered Nechako white sturgeon populations, and sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Progressing downstream, there was an increase in sediment derived from erosion processes on agriculture and forested landscapes consistent with the changing land use in the catchment. Gateuille et al (2019) also found that the construction of a dam in the 1950s resulted in a significant alteration of the sediment transport capacity in the Nechako River Basin, resulting in a change in sediment source dynamics. Overall, Gateuille et al (2019) demonstrated that the sediment source fingerprinting technique can be utilized to investigate how the cumulative effects of anthropogenic and natural disturbances affect sediment source dynamics in a large river basin over short (i.e., annual) and longer (i.e., decadal) temporal scales.…”
Section: Sediment Source Fingerprinting In the Critical Zonementioning
confidence: 94%
See 3 more Smart Citations
“…Progressing downstream, there was an increase in sediment derived from erosion processes on agriculture and forested landscapes consistent with the changing land use in the catchment. Gateuille et al (2019) also found that the construction of a dam in the 1950s resulted in a significant alteration of the sediment transport capacity in the Nechako River Basin, resulting in a change in sediment source dynamics. Overall, Gateuille et al (2019) demonstrated that the sediment source fingerprinting technique can be utilized to investigate how the cumulative effects of anthropogenic and natural disturbances affect sediment source dynamics in a large river basin over short (i.e., annual) and longer (i.e., decadal) temporal scales.…”
Section: Sediment Source Fingerprinting In the Critical Zonementioning
confidence: 94%
“…Gateuille et al (2019) also found that the construction of a dam in the 1950s resulted in a significant alteration of the sediment transport capacity in the Nechako River Basin, resulting in a change in sediment source dynamics. Overall, Gateuille et al (2019) demonstrated that the sediment source fingerprinting technique can be utilized to investigate how the cumulative effects of anthropogenic and natural disturbances affect sediment source dynamics in a large river basin over short (i.e., annual) and longer (i.e., decadal) temporal scales. Gellis et al (2019) apportion sediment using elemental analysis and the sediment fingerprinting approach and age-date sediment with fallout radionuclides in the agricultural Walnut Creek Basin (Iowa, USA).…”
Section: Sediment Source Fingerprinting In the Critical Zonementioning
confidence: 94%
See 2 more Smart Citations
“…For example, Motha, Wallbrink, Hairsine, and Grayson () and Collins, Walling, Webb, and King () used source group means and standard deviations and this approach remains widely used in international literature (e.g. Aliyanta & Sidauruk, ; Brosinsky, Foerster, Segl, & Kaufmann, ; Chen, Fang, & Shi, ; Dahmardeh Behrooz, Gholami, Telfer, Jansen, & Fathabadi, ; Gateuille et al, ). Krause, Franks, Kalma, Loughran, and Rowan (), Wilkinson et al (); Wilkinson, Hancock, Bartley, Hawdon, and Keen (), Haddadchi, Olley, and Pietsch (, ), Laceby and Olley () and Palazón et al () all used a Student's t ‐distribution which gave more weighting to the tails of the distribution than a normal distribution and was considered more appropriate when sample numbers were low.…”
Section: Introductionmentioning
confidence: 99%